Rancang Bangun Alat Ukur Viskositas Digital Pada Oli Menggunakan Sensor Efek Hall - Hasugian , Ruth Nelly (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2020)
Engine oil on motorcycle serves as lubricating oil, coolant, rust protection, cleaning and slit cover on the machine wall. Engine lubrication is used to avoid direct friction between metal in the machine so that metal wear rate and engine damage rate can be reduced. To get the lubricating oil in accordance with the type of vehicle engine used there are some things that must be considered. One of them is the viscosity level of lubricating oil. The viscosity factor of oil is the amount to be adjusted to the machine classification. But the common people choose oil only based on the brand or price offered by the manufacturer. In this final project will be implemented a measurement system of oil viscosity sensor using concentric cylinder method. The method uses two concentric cylinders of different sizes with the space between the two cylinders filled with the liquid to be tested. The outer cylinder or rotor is rotated using a DC motor with a constant velocity and the torque generated from the inner cylinder or stator is measured using a hall effect sensor. The viscosity measurements were carried out on SAE 20W-40 oil and SAE 10W-30 oil by providing constant motor rotation speed and temperature at 27oC. Experimental results at 27oC fluid temperature and 68 Hz motor rotation speeds show the SAE 20W-40 viscosity value of 162.1 centiPoise and SAE 10W-30 oil viscosity of 123.8 centiPoise. Experimental results show that the more viscous the oil the DC motor rotation speed is getting smaller.